Reaction of the Aswaja Group to the Wahhabism Movement in Aceh - Muammar Muammar (Al-Fikrah, 2023)
The discussion on Wahhabism is not a new discussion for the people of Aceh, since the PUSA era this discussion has been developed, because the PUSA was "accused" by traditional clerics of carrying out the Wahhabi movement in Aceh. This movement is now being resurfaced when those who call themselves Aswaja lovers see the existence of Wahhabism and the Wahhabi movement preaching throughout Aceh. According to Aswaja, the Wahhabi missionary movement is contrary to Islamic values ​​and the creeds that are adhered to by the people of Aceh. In this context, Aswaja’s  claim to be heretical is increasing along with the high Wahhabi preaching. In Aswaja’s  view, Wahabime in Aceh has started to gain momentum because they have controlled a number of mosques to spread their da’wah, so that several mosques have become a bone of contention between Aswaja and Wahhabis and a number of recitation sessions have been forcibly disbanded by the Aswaja group. Aswaja’s  contest with Wahhabism in Aceh is now a little disturbing to the social and religious fabric of society, because various accusations of heresy and infidel have finally become words commonly heard in society. The implications for the wahabism movement became even worse when the Aceh government established the criteria for the Aswaja creed through the MPU fatwa No. 04 of 2011. With the issuance of this fatwa, all schools whose aqidah is not in accordance with Aswaja must be rejected from developing in Aceh. Aswaja’s  contest with Wahhabism in Aceh is now a little disturbing to the social and religious fabric of society, because various accusations of heresy and infidel have finally become words commonly heard in society. The implications for the wahabism movement became even worse when the Aceh government established the criteria for the Aswaja creed through the MPU fatwa No. 04 of 2011. With the issuance of this fatwa, all schools whose aqidah is not in accordance with Aswaja must be rejected from developing in Aceh. Aswaja’s  contest with Wahhabism in Aceh is now a little disturbing to the social and religious fabric of society, because various accusations of heresy and infidel have finally become words commonly heard in society. The implications for the wahabism movement became even worse when the Aceh government established the criteria for the Aswaja creed through the MPU fatwa No. 04 of 2011. With the issuance of this fatwa, all schools whose aqidah is not in accordance with Aswaja must be rejected from developing in Aceh.